(untitled) (Ustozlar uchun, 2025)
Abstract: This article examines the most pressing global and local challenges of the 21st century and their adverse effects on the human body. Environmental issues, climate change, urbanization, nutritional imbalances, psychological stress, pandemics, and the growing prevalence of chronic diseases are analyzed in detail. Based on a review of scientific literature, the physiological and psychological impacts of these factors on human health are discussed. The article also explores specific implications for Central Asia, particularly Uzbekistan, where ecological degradation, water scarcity, and urbanization intensify health risks. Finally, recommendations are provided for mitigating these effects, emphasizing sustainable development, health education, and preventive strategies to protect public health.